Package modular-thm: Properties of modular arithmetic

Information

namemodular-thm
version1.66
descriptionProperties of modular arithmetic
authorJoe Leslie-Hurd <joe@gilith.com>
licenseMIT
provenanceHOL Light theory extracted on 2014-11-01
checksumd3529917c7f6faab24ed2dbcd3d5b4a215d1ccc0
requiresbase
modular-def
showData.Bool
Number.Modular
Number.Natural

Files

Theorems

x. x x

fromNatural modulus = 0

x. ¬(x < x)

x. toNatural x < modulus

~0 = 0

x. ~~x = x

x. x + 0 = x

x. x 1 = x

x. 0 + x = x

x. toNatural x div modulus = 0

x. x * 0 = 0

x. x + ~x = 0

x. 0 * x = 0

x. ~x + x = 0

x. toNatural x mod modulus = toNatural x

x. x * 1 = x

x. 1 * x = x

x y. x * y = y * x

x y. x + y = y + x

x. fromNatural x = 0 divides modulus x

x y. ¬(x < y) y x

x y. ¬(x y) y < x

x. ~x = 0 x = 0

x y. x * ~y = ~(x * y)

x y. ~x * y = ~(x * y)

x y. ~x = ~y x = y

x y. toNatural x = toNatural y x = y

m n. fromNatural (m n) = fromNatural m n

x y. x + y = x y = 0

x y. y + x = x y = 0

x y. ~x + ~y = ~(x + y)

x y. toNatural (x * y) = toNatural x * toNatural y mod modulus

x y. toNatural (x + y) = (toNatural x + toNatural y) mod modulus

x y z. x * y * z = x * (y * z)

x y z. x + y + z = x + (y + z)

x y z. x + y = x + z y = z

x y z. y + x = z + x y = z

x1 x2 x3. x1 < x2 x2 < x3 x1 < x3

x1 x2 x3. x1 < x2 x2 x3 x1 < x3

x1 x2 x3. x1 x2 x2 < x3 x1 < x3

x1 x2 x3. x1 x2 x2 x3 x1 x3

n. 0 n = if n = 0 then 1 else 0

x y. fromNatural x = fromNatural y x mod modulus = y mod modulus

x y z. x * (y + z) = x * y + x * z

x y z. (y + z) * x = y * x + z * x

x m n. x m * x n = x (m + n)

External Type Operators

External Constants

Assumptions

bit0 0 = 0

n. n n

modulus mod modulus = 0

0 mod modulus = 0

t. (x. t) t

() = λp. p = λx.

t. ¬¬t t

x. fromNatural (toNatural x) = x

n. 0 * n = 0

n. 0 + n = n

n. n mod modulus < modulus

n. bit1 n = suc (bit0 n)

m. m 0 = 1

m. 1 * m = m

() = λp q. p q p

x. x 0 = 1

n. toNatural (fromNatural n) = n mod modulus

x. ~x = fromNatural (modulus - toNatural x)

m n. m * n = n * m

m n. m + n = n + m

m n. m < n m n

n. divides modulus n n mod modulus = 0

n. n mod modulus mod modulus = n mod modulus

m n. ¬(m < n) n m

() = λp q. (λf. f p q) = λf. f

x y. x < y toNatural x < toNatural y

x y. x y toNatural x toNatural y

m n. m < n m div n = 0

m n. m < n m mod n = m

m n. suc m + n = suc (m + n)

n. 0 n = if n = 0 then 1 else 0

x n. x suc n = x * x n

x1 y1. fromNatural (x1 * y1) = fromNatural x1 * fromNatural y1

x1 y1. fromNatural (x1 + y1) = fromNatural x1 + fromNatural y1

m n. m suc n = m * m n

m n. n m m - n + n = m

m n p. m * (n * p) = m * n * p

m n p. m + (n + p) = m + n + p

m n p. m < n n < p m < p

m n p. m < n n p m < p

m n p. m n n < p m < p

m n p. m n n p m p

p. p 0 (n. p n p (suc n)) n. p n

m n p. m * (n + p) = m * n + m * p

m n p. (m + n) * p = m * p + n * p

b f x y. f (if b then x else y) = if b then f x else f y

m n. (m mod modulus) * (n mod modulus) mod modulus = m * n mod modulus

m n. (m mod modulus + n mod modulus) mod modulus = (m + n) mod modulus